Shallot distribution model under hydroclimatic extremes and soil physical properties in Sleman, Yogyakarta - Umi Munawaroh; Muhamad Khoiru Zaki; Susilowati; Muhammad Rahman Yulianto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Global climate change significantly affects the agriculture sector, including reducing crop productivity and potential distribution through the frequency of hydrometeorological disasters. Despite its economic importance, limited research has explored the effects of such hydroclimatic extremes on shallot (Allium cepa var. aggregatum) cultivation. This study aims to identify the soil-climate conditions, extreme events, variable contributions, and potential distribution areas of shallot in Sleman regency. The MaxEnt model was used herein to predict the suitable distribution area of shallot under hydroclimatic extremes and soil physical properties. The results show that shallot potential distribution in Sleman regency is governed by the synergistic action of climatic extremes and soil physical structure based on MaxEnt analysis. The dominance of Consecutive Dry Days (CDD) and soil moisture underscores the necessity of maintaining a stable soil–water equilibrium under intensifying hydroclimatic variability. These insights support the use of high-resolution soil and climate mapping to inform adaptive irrigation scheduling, precision tillage, and organic amendment strategies. Keywords: Climate change; extreme events, maximum entropy, soil properties, species distributions